The effect of situation awareness on driving performance in young sleep-deprived drivers. (July 2021) - Wijayanto, Titis; Marcillia, Syam Rachma; Lufityanto, Galang; Wisnugraha, Bonifatius Bramantya; Alma, Tasya Ghonia; Abdianto, Rayanda Utomo
Abstract: This study aims to investigate how situation awareness (SA) when driving in sleep-deprived condition mediates the effect of sleep deprivation and driving performance in young drivers. Fifteen male students (mean age 21.1 ± 0.8 years) underwent two 45-min driving simulation sessions in random counterbalanced order: one in the morning after approximately seven hours sleep (normal-sleep condition) and another one in the morning after 24 h sleep deprivation (sleep-deprived condition). SA was measured using quantitative analysis of situation awareness (QASA). Driving performance was measured in terms of the number of collisions. Here we find that SA and driving performance decrement when driving in sleep-deprived condition. Compared to normal-sleep condition, driving in sleep-deprived condition impaired SA ( p =  0.024) and driving performance ( p  = 0.006). The mediation analysis shows that the decrement of driving performance is predicted by sleep deprivation ( p =  0.021) and SA ( p  = 0.041). These results indicate that SA partially mediates the effect of sleep deprivation on driving performance. SA decrement in sleep-deprived condition impairs driving performance that can pose a danger to safety-critical action during driving in young drivers. Highlights: The relationship between situation awareness (SA) and driving performance in young sleep deprived drivers was investigated. Sleep deprivation protocol in this study impaired SA and driving performance in young drivers. SA partially mediates the effect of sleep deprivation on driving performance. Driving performance impairement due to SA decrement in sleep-deprived condition can pose a danger to safety-critical action.